2015
DOI: 10.1016/j.meegid.2014.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the source of A (H10N8) virus causing human infection

Abstract: A novel H10N8 influenza A virus has been detected in three humans in China since December 2013. Although this virus was hypothesized to be a novel reassortant among influenza viruses from wild birds and domestic poultry, its evolutionary path leading to human infection is unknown. Sporadic surveillance at the live poultry market (LPM) suspected to be the source of infection for the first H10N8 patient has shown a gradual increase in influenza virus prevalence culminating with a predominance of H10N8 viruses. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Among the 49 samples from Nanchang, 44 were described in previous study and 30 were successfully sequenced samples included 18 H10, 2 H6, and 10 H9 subtypes of IAVs. Results from this study showed that, in addition to those H10 reported before (Xu et al, 2015), 7 more samples from Nanchang were identified as H10 positive. Taken together, 25 (51.0%) of 49 samples from Nanchang were H10 positive, as were confirmed by genomic sequencing (Eurofins MWG Operon Inc., Huntsville, AL, USA).…”
Section: Dear Editorsupporting
confidence: 57%
See 2 more Smart Citations
“…Among the 49 samples from Nanchang, 44 were described in previous study and 30 were successfully sequenced samples included 18 H10, 2 H6, and 10 H9 subtypes of IAVs. Results from this study showed that, in addition to those H10 reported before (Xu et al, 2015), 7 more samples from Nanchang were identified as H10 positive. Taken together, 25 (51.0%) of 49 samples from Nanchang were H10 positive, as were confirmed by genomic sequencing (Eurofins MWG Operon Inc., Huntsville, AL, USA).…”
Section: Dear Editorsupporting
confidence: 57%
“…The viruses marked in blue indicate those detected previously (Xu et al, 2015); the viruses marked in red indicate those newly detected by qRT-PCR in this study; the human origin A/Jiangxi-Donghu/346/2013 (H10N8) virus was marked in green. GenBank accession numbers are included at the end of each virus name.…”
Section: Figurementioning
confidence: 82%
See 1 more Smart Citation
“…Our previous analysis of 571 H9N2 viruses showed a high degree of genetic heterogeneity: a total of 98 genotypes were represented among the 571 viruses (Dong et al, 2011). In China, H9N2 viruses have been prevalent since the mid-1990s (Sun et al, 2010), and among those isolated from chickens, a total of 69 genotypes have been confirmed, one of which contributed all six of its internal genes to the novel H7N9 virus and H10N8 virus (Pu et al, 2015;Xu et al, 2015). A few H9N2 viruses have been isolated from wild birds in China, and most that have been isolated were clearly different from poultry-derived H9N2 viruses (Wang et al, 2014a;Zhu et al, 2013Zhu et al, , 2014.…”
Section: Introductionmentioning
confidence: 96%
“…Regarding A(H10N8) infection, three human cases have been confirmed in Jiangxi Province in China since December 2013 . All three cases had severe bilateral pneumonia and two died.…”
Section: Avian Influenzamentioning
confidence: 99%